Konsep Pemikiran Ekonomi Islam Era Bani Umayah dan Relevansi dengan Masa Sekarang - Muhammad Haris Hidayatulloh; Muhtadi Ridwan; Khusnuddin Khusnuddin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to provide an overview in the form of portraits of the thoughts of the Umayyad caliphs and what policies were implemented at that time, and what kind of relevance that can be made to the present. With this research concept, this journal uses qualitative research methods or literature study by collecting data both from books and articles related to that title. The results of this study found that the relevance that existed during the caliph era to the present that was most prominently applied was related to the issue of zakat and al Kharaj (tax). Of the two objects, the implementation that is happening at the present time is still not optimally carried out, of course this is because of the many problems that are occurring with the present. Not with the period when Umar bin Abdul Aziz led during the Umayyad dynasty, where economic inequality practically did not exist. Therefore, it needs to be implemented and maximized at the present time to optimize these two aspects, of course this is not impossible, especially since Indonesia is known for its predominantly Muslim population, of course this is very possible.” Keywords: Islamic Economic Thought, Umayyads, relevance.